Genetic ablation of tau mitigates cognitive impairment induced by type 1 diabetes - Abbondante, Serena; Baglietto-Vargas, David; Rodriguez-Ortiz, Carlos J; Estrada-Hernandez, Tatiana; Medeiros, Rodrigo; LaFerla, Frank (Elsevier, 2014)
Patients affected by diabetes show an increased risk of developing Alzheimer disease (AD). Similarly, patients with AD show impaired insulin function and glucose metabolism. However, the underlying molecular mechanisms connecting these two disorders are still not well understood. Herein, we investigated the microtubule-associated protein tau as a new link between AD and diabetes. To determine whether diabetes causes cognitive decline by a tau-dependent mechanism, we treated non-transgenic (Ntg) and tauknockout mice with streptozotocin, causing type 1 diabetes-like disease (T1D). Interestingly, although induction of T1D in Ntg mice led to cellular and behavioral deficits, it did not do so in tau-knockout mice. Thus, data suggest that tau is a fundamental mediator of the induction of cognitive impairments in T1D. Tau dysregulation, which causes a reduction in synaptic protein levels, may be responsible for the cognitive decline observed in Ntg streptozotocin-treated mice. Concomitantly, we demonstrate the novel finding that depletion of endogenous tau mitigates behavioral impairment and synaptic deficits induced in T1D-like mice. Overall, our data reveal that tau is a key molecular factor responsible for the induction of cognitive deficits observed in T1D and represents a potential therapeutic target for diabetes and patients with AD.
Keywords: Diabetes; Tau; Diabetes type 1; Cognitive impairments